An imperial laboratory: the investigation and treatment of treponematoses in occupied Haiti, 1915-1934 - Antony Dalziel McNeil Stewart (História, Ciências, Saúde: Manguinhos)
This article examines anti-treponematoses work as part of US occupation public health policy in Haiti, a unique event in the history of international health. Yaws was highly prevalent in Haiti, but occupation doctors initially ignored it because of its close association with syphilis and stigmas attached to sexually transmitted disease. This changed when C.S. Butler asserted that yaws was “innocent” and that the two diseases should therefore be considered as one. Treatment increased as an anti-treponematoses campaign was now believed to hold great benefits for the occupation’s paternalist and strategic aims, even though it ultimately failed. This work reflected Haiti’s status as a public health “laboratory” which affected Haitian medicine for years to come and significantly influenced future campaigns aimed at disease eradication.